2021
DOI: 10.1136/bjophthalmol-2021-319307
|View full text |Cite
|
Sign up to set email alerts
|

Myopia incidence and lifestyle changes among school children during the COVID-19 pandemic: a population-based prospective study

Abstract: BackgroundThe impacts of social restrictions for COVID-19 on children’s vision and lifestyle remain unknown.AimsTo investigate myopia incidence, spherical equivalent refraction (SER) and lifestyle changes among schoolchildren during the COVID-19 pandemic.MethodsTwo separate longitudinal cohorts of children aged 6–8 years in Hong Kong were included. The COVID-19 cohort was recruited at the beginning of the COVID-19 outbreak, whereas the pre-COVID-19 cohort was recruited before the COVID-19 pandemic. All childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
185
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 118 publications
(197 citation statements)
references
References 24 publications
9
185
1
2
Order By: Relevance
“…Children's lifestyles have changed among children during the COVID-19 pandemic ( 12 , 30 ). During the study-at-home period, students were away from the school classrooms and engaged in online education, which greatly increased digital screen time.…”
Section: Discussionmentioning
confidence: 99%
“…Children's lifestyles have changed among children during the COVID-19 pandemic ( 12 , 30 ). During the study-at-home period, students were away from the school classrooms and engaged in online education, which greatly increased digital screen time.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain why the difference between DIMS and SVL groups in the current analysis is lower than in the previous study. 27 It is also worth noting that previous longitudinal studies 14 , 15 on refractive error change during the COVID-19 lockdown were targeting whole cohorts (ie, including children with and without myopia). From the current results on children with myopia, we speculate that the drastic change in environmental risk factors during the lockdown period 4 were associated with myopic shift in people without myopia and myopia progression in those with myopia.…”
Section: Discussionmentioning
confidence: 99%
“…Although a previous cross-sectional study 28 revealed an increase in myopia prevalence and incidence during the COVID-19 pandemic compared with historical numbers and some recent studies 14 , 15 longitudinally following up total cohorts of children, the current study leveraged data from longitudinal studies that were prospectively conducted during the pandemic in school-aged children with myopia requiring optical correction. Using exploratory, prespecified analyses, the association of lockdown measures on myopia progression was evaluated, in addition to the performance of DIMS spectacle lenses for control of myopia progression during the COVID-19–induced lockdown period.…”
Section: Introductionmentioning
confidence: 99%
“…pandemic, the myopia rate in primary and middle school students increased by 11.7% over a 6 month period in China (sohu.com/a/41512 7992_105067), while other countries also saw marked rises. [6][7][8][9][10] In particular, the results of a survey released by the Chinese Ministry of Education at the end of August 2020 highlighted the problem of myopia.…”
mentioning
confidence: 99%